2015
DOI: 10.1614/ws-d-13-00062.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Methods for Crop–Weed Competition Studies

Abstract: The annual global economic loss caused by weeds has been estimated at more than $100 billion U.S. dollars (Appleby et al. 2000). Additionally, worldwide annual herbicide sales are in the range of U.S. $25 billion (Agrow 2003). In light of these large dollar figures, it becomes clear that a greater understanding of crop—weed interactions is essential in order to develop cost-effective and sustainable weed management practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
132
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 47 publications
1
132
0
4
Order By: Relevance
“…Under field conditions, weeds compete with the target crop for resources necessary for growth and development, and subsequently reduce crop yield (Swanton et al, 2015). Under field conditions, weeds compete with the target crop for resources necessary for growth and development, and subsequently reduce crop yield (Swanton et al, 2015).…”
Section: Weed Biomassmentioning
confidence: 99%
“…Under field conditions, weeds compete with the target crop for resources necessary for growth and development, and subsequently reduce crop yield (Swanton et al, 2015). Under field conditions, weeds compete with the target crop for resources necessary for growth and development, and subsequently reduce crop yield (Swanton et al, 2015).…”
Section: Weed Biomassmentioning
confidence: 99%
“…Nitrogen (N) is one of the most important agricultural inputs that influences the crop-weed interference (Swanton et al 2015). Previous studies on the effect of N rate on crop-weed competition have shown variable outcomes.…”
mentioning
confidence: 99%
“…An additive design (Swanton et al, 2013) was utilized for this experiment, where hybrid or shattercane densities varied while that of sorghum remained constant. The treatment design was a factorial with two weedy genotypes, shattercane and hybrid, with the hybrid being either exposed or not exposed to a herbicide application (total of three treatment levels), and five www.ccsenet.org/jas Journal of Agricultural Science Vol.…”
Section: Greenhouse Experiments and Data Collectionmentioning
confidence: 99%
“…than wheat (Triticum aestivum L.). Additive designs, where crop density is held constant while weed density varies (Swanton, Nkoa, & Blackshaw, 2013), have been widely used in field and greenhouse studies looking at yield loss-weed density relationships because they accurately reflect the reality that weeds occur within a crop planted at constant density.…”
Section: Introductionmentioning
confidence: 99%